1984
DOI: 10.1002/cd.23219842404
|View full text |Cite
|
Sign up to set email alerts
|

Marital discord and children: Problems, strategies, methodologies, and results

Abstract: In Chapter One, Hetherington cautioned against becoming too attached tc methods of research. I think this fierce attachment is true of those of us whc use observational methodology in clinical/developmental research. I spent approximately ten years in observational work; a large portion of that was spent on methodological problems, particularly observer drift, shift, drop; reactivity in classrooms; and various types of reliability estimates that one carr make (OLeary and Johnson, 1979). Now I agree with Hether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In keeping with other research and clinical observation (Jouriles & LeCompte, 1991;O'Leary, 1984;Trickett & Susman, 1989), the results of the present study indicate that child gender moderates the relationship between the battering of women and aggression toward children. Specifically, within families characterized by more extreme battering, both fathers and mothers are more aggressive toward sons than toward daughters.…”
Section: Discussionsupporting
confidence: 90%
“…In keeping with other research and clinical observation (Jouriles & LeCompte, 1991;O'Leary, 1984;Trickett & Susman, 1989), the results of the present study indicate that child gender moderates the relationship between the battering of women and aggression toward children. Specifically, within families characterized by more extreme battering, both fathers and mothers are more aggressive toward sons than toward daughters.…”
Section: Discussionsupporting
confidence: 90%
“…Those interested in indirect effects have primarily focused on the behavior and perceptions of parents toward their children as a response to spousal hostility. They have observed that marital conflict creates a situation in which parents become increasingly involved with their own problems, depleting themselves of the emotional resources necessary to effectively monitor their children (Patterson & Southamer-Loeber, 1984), causing them to emotionally withdraw from their children (Dickstein & Parke, 1988), leading them to resent children reminiscent of a spouse (O'Leary, 1984) and leading them to treat children in an angry or hostile manner (Engfer, 1988;Jouriles, Murphy, & O'Leary, 1989;Kerig, Cowan, & Cowan, 1993).…”
Section: Adjustment: Direct and Indirect Effectsmentioning
confidence: 99%
“…Researchers in the area have argued the need for greater specificity in assessing the different dimensions of interparental conflict that might affect child development (Forehand & McCombs, 1989;Jouriles, Murphy, et al, 1991;Katz & Gottman, 1993). Dimensions of interparental conflict that have received attention include intensity, frequency, and the degree to which parents' quarrels are threatening to the child (Grych & Fincham, 1993;Grych, Seid, & Fincham, 1992), the degree to which conflicts are resolved (J. S. Cummings, Simpson, & Wilson, 1993;Grych et al, 1992), whether the content of conflicts concerns the child (Jouriles, Murphy, et al, 1991;Snyder, Klein, Gdowski, Faulstich, & LaCombe, 1988), and the degree to which arguments occur in the child's presence (J. S. Cummings, Pellegrini, Notarius, & Cummings, 1989;Emery & O'Leary, 1982;O'Leary, 1984;Porter & O'Leary, 1980). In particular, it may be the way in which problems in the marriage spill over into the parent-child relationship that accounts for the influence of marital discord on child development (Camara & Resnick, 1989;Engfer, 1988;Fauber, Forehand, Thomas, & Wierson, 1990;Westerman & Schonholtz, 1993).…”
mentioning
confidence: 99%